Short-Course Chemotherapy Regimens for Treatment of Multiple and Pre-Extensive Drug Resistant Tuberculosis in Combination with Surgery in Older Children and Adolescents - E. S. Ovsyankina; L. V. Panova; E. A. Krushinskaya; M. A. Bagirov (Туберкулез и болезни лёгких)
The objective: to evaluate the eﬀectiveness of short-curse chemotherapy regimens for treatment of MDR/pre-XDR tuberculosis in combination with surgery in older children and adolescents.Subjects and Methods. 51 patients with MDR/pre-XDR respiratory tuberculosis aged 13-17 years were enrolled in a prospective open study (2017-2021). The statistical correlation between certain factors and prescription of continuous or short-course chemotherapy to a patient after surgery was calculated using the Pearson χ² test.Results. Of the 51 patients, short-course chemotherapy regimen (12 months) was administered to 37 (72.5%) patients, while continuous treatment regimen (13 months or more) was used in 14 (27.5%) patients. It was found that surgical treatment was taken into account as a risk factor when prescribing continuous chemotherapy (χ² = 5.307; p = 0.022). In 40 operated patients, continuous chemotherapy was statistically signiﬁcantly more often prescribed when following factors were observed: surgery after 10 months and more after the start of treatment (χ² = 21.567; p < 0.001), two-stage surgery (χ² = 8.254; p = 0.005), and tuberculosis progression after surgery (χ² = 3.910; p = 0.049). TB relapses after a year of follow-up in the patients treated with continuous chemotherapy regimens made 11%, while in case of short-course treatment, they were 9%. The results of our study indicate the possibility of using short-course chemotherapy regimens in combination with surgical treatment.